PENGARUH PENAMBAHAN BUTON GRANULAR ASPHALT PADA CAMPURAN BETON ASPAL TERHADAP MODULUS RESILIEN DAN GRADASI - Heddy R. Agah; Sigit P. Hadiwardoyo (Jurnal Transportasi, 2012)
Buton Asphalt is a natural asphalt which has advantages because it contains minerals and asphalt, even though its asphalt content does not completely meet the specification as a binder of asphalt concrete. Various studies of the Buton Asphalt usage have been carried out. This paper presented the results of a study on asphalt concrete mixtures using materials of Buton Granular Aggregate (BGA), treating the BGA as aggregates, with the BGA content of 5% and 7%. Mixtures and specimens were analyzed to investigate the effects of BGA on the performance of asphalt concrete. The results showed that the indirect tensile strength for the mixture with BGA of 5% is higher than that obtained in the those with BGA content of 7%.Keywords: natural asphalt, asphalt concrete, Buton Granular Asphalt, indirect tensile strength.